BEHAVIORAL ACCOUNTING: THE BEHAVIORAL IMPACT OF FISHERIES SOCIAL ASSISTANCE RECIPIENTS OF ARU ISLANDS REGENCY WITH A PLANNED BEHAVIOR THEORY APPROACH - Warkula, Yohanes Zefnath; Mediaty; T. Pontoh, Grace (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2023)
This study aims to determine how the impact of accounting behavior related to financial attitudes, financial literacy, and financial experience of recipients of fisheries social assistance funds of the Aru Islands Regency Government using the Theory of Planned Behavior (TPB) on fishermen groups. The method in this study is qualitative descriptive research with a phenomenological approach, the approach in this study using phenomenological methods is trying to understand the meaning of various events and human interactions in certain situations. The results of this study suggest that financial attitudes, literature, and experience can be the drivers of financial behavior in Planned Behavior Theory (TPB) is a continuation of the theory of reasoned action required by the limitations of the original model of behavior in which limited humans will control financial behavior. The contribution of good research to the Theory of Planning Behavior (TPB) is to develop attitudes, literacy, and experience in managing the finances of fisheries social assistance funds by fishermen groups of the Aru Islands Regency Government so that the reporting of social assistance fund accountability has value and is systematized by the nature of the accountability report of the Aru Islands Regency Government.